Do individuals' resist green home investment decisions? An empirical study from status quo bias and inertia perspective - R, Sharmila Devi; Perumandla, Swamy (Frontiers in Sustainable Cities, 2023)
The study explores the influence of Status Quo Bias theory constructs and inertia on resistance to sustainable green home investment among Indian homeowners and prospective homebuyers.The collection of survey data through a questionnaire administered to 404 participants has involved, and data analysis was performed using Partial Least Squares Structural Equation Modeling (PLS SEM). Factors such as loss aversion, transition costs, adherence to social norms, and self-efficacy to change significantly contribute to resistance. Inertia amplifies the relationship between transition costs, social norms, and self-efficacy to change, but does not mediate loss aversion. The research highlights the importance of providing clear information about the benefits of green home upgrades and offering incentives to reduce perceived costs and risks. It also addresses environmental sustainability concerns and the increasing importance of green home investment decisions in today's world.